2010
DOI: 10.1073/pnas.0910261107
|View full text |Cite
|
Sign up to set email alerts
|

Surgery with molecular fluorescence imaging using activatable cell-penetrating peptides decreases residual cancer and improves survival

Abstract: The completeness of tumor removal during surgery is dependent on the surgeon's ability to differentiate tumor from normal tissue using subjective criteria that are not easily quantifiable. A way to objectively assess tumor margins during surgery in patients would be of great value. We have developed a method to visualize tumors during surgery using activatable cell-penetrating peptides (ACPPs), in which the fluorescently labeled, polycationic cell-penetrating peptide (CPP) is coupled via a cleavable linker to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
310
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 441 publications
(316 citation statements)
references
References 22 publications
(36 reference statements)
3
310
0
1
Order By: Relevance
“…Ce complexe ne pénètre pas efficacement dans les cellules non tumorales, mais le clivage du linker par des protéases spécifiques de la tumeur libère le CPP-Cy5 qui pénètre dans les cellules tumorales, marquant ainsi très efficacement la tumeur in vivo. L'équipe a ainsi pu montrer que quand la chirurgie est effectuée en présence de ce complexe de pénétration cellulaire, il y a dix fois moins de cellules tumorales résiduelles que lors d'une chirurgie classique [43]. Tsien a obtenu le prix Nobel de chimie en 2008 pour l'ensemble de ses travaux sur la conception de molécules fluorescentes et photolabiles [57].…”
Section: Délivrer Des Nanoparticulesunclassified
“…Ce complexe ne pénètre pas efficacement dans les cellules non tumorales, mais le clivage du linker par des protéases spécifiques de la tumeur libère le CPP-Cy5 qui pénètre dans les cellules tumorales, marquant ainsi très efficacement la tumeur in vivo. L'équipe a ainsi pu montrer que quand la chirurgie est effectuée en présence de ce complexe de pénétration cellulaire, il y a dix fois moins de cellules tumorales résiduelles que lors d'une chirurgie classique [43]. Tsien a obtenu le prix Nobel de chimie en 2008 pour l'ensemble de ses travaux sur la conception de molécules fluorescentes et photolabiles [57].…”
Section: Délivrer Des Nanoparticulesunclassified
“…In a preclinical study on the efficacy of resection surgery guided by ACPPDs linked to Cy5, a fluorescent dye, and gadolinium, the authors found that this procedure on mice suffering from melanoma yielded a better prognosis (100% higher eight month progression-free survival and 50% higher overall survival) than mice subjected to white light surgery [15]. The drastic improvement in prognosis is due to a 10-fold increase in ACPPDs in subjects with complete resection compared to the group that underwent white light surgery and the procedure's 93% specificity rate [15]. ACPPs can also aid in evaluating the presence of cancer in lymph nodes during surgery, which is vital to the progression of the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…In order for ACPPs to enter their active state and translocate into tumor cells, the bond between the polyanionic peptide and the polycationic peptide, which is coupled to the cargo, must undergo proteolytic cleavage by matrix metalloproteinases (MMP). MMP2 and MMP9, which are proteases overexpressed in several types of cancer, are integral for tumorigenesis due to their ability to degrade extracellular matrices, induce angiogenesis, and promote growth factors [15]. The degree of MMP2 and MMP9 expression is contingent on the magnitude of tumor malignancy (the higher the grade of tumor, the higher expression of these proteins), and the enzymes have highly specific binding sites for substrates, thus making them robust targets for identifying cancer [15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations